2016
DOI: 10.1186/s12905-016-0321-7
|View full text |Cite
|
Sign up to set email alerts
|

Family planning use and associated factors among pastoralist community of afar region, eastern Ethiopia

Abstract: BackgroundEthiopia is the second most populous country in Africa with a total fertility rate (TFR) of 4.8 children per a woman and contraceptive prevalence rate (CPR) of 29 %. The overall prevalence of modern family planning in a pastoralist community, like Afar region, is low (9.1 %). This study aimed to assess family planning utilization and associated factors among married women of Afar region, Eastern Ethiopia.MethodsA community-based cross-sectional study was conducted from January 10-28, 2013 among 602 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
62
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 7 publications
(7 reference statements)
17
62
2
1
Order By: Relevance
“…And this is in line with previous studies that reported a large number of couples who desired FP services was not receiving the service for a variety of reasons including religious oppositions, especially in the rural remote areas where the media is still not reaching and influencing mindset [4, 21, 23]. Therefore oppositions either due to religious beliefs, or concern of societal objection could be one of the major reasons for less use of modern contraceptive methods by pastoralist women in the Bale eco-region despite the women’s fertility desire.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…And this is in line with previous studies that reported a large number of couples who desired FP services was not receiving the service for a variety of reasons including religious oppositions, especially in the rural remote areas where the media is still not reaching and influencing mindset [4, 21, 23]. Therefore oppositions either due to religious beliefs, or concern of societal objection could be one of the major reasons for less use of modern contraceptive methods by pastoralist women in the Bale eco-region despite the women’s fertility desire.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Polygyny has implications for coital frequency and, therefore, fertility. Both early marriage and polygynous union in the study area were more than the national rural levels of (16.5 years) mean age at first marriage and (12%) of polygynous union reported in the 2011 Ethiopian demographic and health survey [6], this also agree with findings from Afar regions, Ethiopia that revealed (95%) of early marriage by pastoralist women [21]. The women age at their first marriage was against the Ethiopian Revised Family Code Proclamation, which declares that the minimum age at first marriage is 18 for both sexes [22].…”
Section: Discussionsupporting
confidence: 87%
“…This illustrates male involvement is feasible and brings a remarkable change in the pastoralist context. It should be noted, married women in our study embedded in strong religious and cultural perspectives which favors a large family size, high husband objection for not practicing of FP and poor decision-making for FP use (9,10,26). Moreover, all aspects of the health and wellbeing of the pastoralist women strongly affected by religious perspective and belief -(18)-and the community believed that all health problems are caused by supernatural forces (38).…”
Section: Discussionmentioning
confidence: 95%
“…We developed a questionnaire for the purpose of this study and attached as Additional File 1. The developed tool was piloted in 10% of the sample after it was developed by reviewing different literature on the previous nding that aims to explore barriers and facilitators to Reproductive Maternal Neonatal Health (RMNH) services including FP (6,9,10,26). The collected piloted tool was exposed to a reliability test.…”
Section: Data Collection Tool and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation